Sort by

- Relevance
- |Time

p = 1 / [ √(1 - (

**v**^2/c^2)) ] p [ √(1 - (**v**^2/c^2)) ] = 1 squaring on both sides to get rid of the sq.root p^2 (1- (**v**^2/c^2)) = 1 1 - (**v**^2/c^2) = 1 / p^2**v**^2/c^2 = 1 - (1/p^2)**v**^2 = c^2...3 Answers · Science & Mathematics · 15/05/2008

||

**v**|| = 3 θ = 100° No calculation is needed. To understand this you have to understand components. A vector**v**with magnitude ||**v**|| and direction θ has: x component = ||**v**||cos(θ) y component...2 Answers · Science & Mathematics · 14/07/2015

Let

**v**= (f, g, h). Computing determinants repeatedly yields ∇ x**v**= (h_y - g_z, f_z - h_x, g_x - f_y) ==> ∇ x (∇ x**v**) = ((g_xy - f_yy) - (f_zz - h_xz), -[(g_xx - f_xy) - (h_yz - g_zz)], (f_xz - h_xx...1 Answers · Science & Mathematics · 08/07/2010

50/

**v**= (1/5)^(1/5)**v**= ((1/5)^(1/5)) × 50 Find 50 divided by the fifth... it's a quintic, so there's four other (complex) roots**v**= 50 5^(1/5) This is 50 5^(1/5) 1^(1/5) which is...8 Answers · Science & Mathematics · 08/08/2012

**v**= u + 2w**v**= 2i - j + 2(i + 2j)**v**= 2i -j + 2i + 4j**v**= 4i + 3j2 Answers · Science & Mathematics · 25/06/2011

sec [ arctan(u) + arccos(

**v**)] let arctan(u) = A tan A = u ==> opposite side = u and adjacent side...cos B =**v**-------------(3) ==> sin B = √(1 - cos^2(B)) = √(1 -**v**^2)---------------------(4) now sec [ arctan(u) + arccos(**v**)] = sec [ A + ...1 Answers · Science & Mathematics · 27/07/2010

**V**= integral dxdydz**V**= integral[0 to 1] integral[0 to 1 - x] integral[0 to 1 - y - x] of 1 dzdydx**V**= integral[x = 0 to 1] integral[y = 0 to 1 - x] [z = 0 to 1 - y - x] zdydx**V**...4 Answers · Science & Mathematics · 03/06/2010

sin

**v**+ (cos**v**) / 4 = 0 => sin**v**= - (cos**v**) / 4 => (sin**v**) / (cos**v**) = -1 / 4 => tan**v**= -(1 / 4...by [a^2 + b^2 = c^2], c^2 = 1 + 16 => c = root17 Thus, cos**v**= adjacent / hypotenuse = 4 / root17. Since either [sin**v**] or [cos**v**...2 Answers · Science & Mathematics · 21/09/2008

One possibility is

**v**(x) = x^2 and u(x) = 1/(x + 1), because with this choice you have u(**v**(x)) = 1/(**v**(x...x)) = (u(x))^2 = 1/(x+1)^2. How did I come up with u and**v**? I just stared at the two formulas and thought, for...2 Answers · Science & Mathematics · 26/07/2011

If

**v**is half of w:**v**= w/2 and u is the mean of**v**and w: u = (**v**+ w) / 2 And you know it's a triangle...w = 80 Now that we have w we can solve for**v**and u:**v**+ w = 120**v**+ 80 = 120**v**= 40 u = (**v**+ w...3 Answers · Science & Mathematics · 25/10/2019